Insulin-like growth factor binding protein-1 and insulin in polycystic ovary syndrome: a systematic review and meta-analysis - Jin, Yuxin; Sun, Fei; Yang, Aili; Yu, Xinwen; Li, Yi; Liang, Shengru; Jing, Xiaorui; Wang, Kai; Zhang, Lan; Xiao, Sa; Zhang, WenCheng; Wang, Xiaoguang; et al. (Frontiers in Endocrinology, 2023)
Background Insulin-like growth factor binding protein-1 (IGFBP-1) is considered a decline in polycystic ovary syndrome (PCOS), but it remains controversial that whether such reduction is attributed to obesity.Aims This systematic review aims to explore whether IGFBP-1 is reduced in PCOS, and whether such reduction is associated with obesity.Results Our pooled study included 12 studies with a total of 450 participants. IGFBP-1 levels in PCOS were significantly lower than that in non-PCOS (SMD (95%CI)=-0.49(-0.89, -0.09), P=0.02). No significant difference in IGFBP-1 levels between patients with or without PCOS classified by BMI. Whilst, stratification by PCOS status revealed a significant decrease in IGFBP-1 in overweight (SMD (95%CI)=-0.92(-1.46， -0.37)，P=0.001). When comparing fasting insulin in the same way, PCOS patients had significantly elevated fasting insulin level but not statistically declined IGFBP-1 after classified by BMI.This meta-analysis provides evidence that the decrease of IGFBP-1 in PCOS was more strongly influenced by comorbid obesity than by PCOS itself.Additionally, contrast to previous findings that insulin significantly suppresses IGFBP-1, our results suggested that the suppression of PCOS-related hyperinsulinemia on IGFBP-1 seemed diminished. Overall, our work may provide a novel perspective on the mechanism between insulin and IGFBP-1 underlying PCOS development.